Applying The Integrated Model Of Tourism To Study Impact Of Covid-19 On Algerian Tourism Industry - Ladjali, Adel (جامعة الوادي - University of Eloued, 2022)
Algeria possesses huge and distinct tourism potentials, whether they are natural such as the desert and beaches, historical such as landmarks and events, or modern such as tourist resorts. This is what the government has been exploiting recently to strengthen the Algerian tourism industry. However, the spread of the COVID-19 epidemic had a sudden impact on all economic sectors, including the tourism sector. So that is why this study sought to determine Impact of COVID-19 on Algerian Tourism Industry. In this study, we have adopted the systemic approach via integrated model of tourism, which means study of tourism is as a set of integrated layers to determine the different impacts of COVID-19 on Algerian Tourism Industry. To achieve the above objectives, we have taken the statistics of Algerian tourism during period of 2015-2020, from ministry of Algerian tourism. After analyze the data, the study has reached the following conclusion: 1. Because of COVID-19, the most affected Layer in the integrated model of tourism is the travelers layer; 2. Declining the layer of travelers does not necessarily lead to the decline of all layers of the integrated model of the Algerian tourism industry.
مقال
Keywords: tourism ; integrated model ; Algeria ; COVID-19